Re-storying autism: a body becoming disability studies in education approach. Issue 5 (16th April 2021) - Douglas, P.; Rice, C.; Runswick-Cole, K.; Easton, A.; Gibson, M. F.; Gruson-Wood, J.; Klar, E.; Shields, R.
ABSTRACT: This paper presents and analyzes six short first-person films produced through a collaborative multimedia storytelling workshop series focused on experiences of autism, education and inclusion. The aim of the project is to co-create new understandings of autism beyond functionalist and biomedical ones that reify autism as a problem of disordered brains and underpin special education. We fashion a body becoming disability studies in education approach to proliferate stories of autism outside received cultural scripts – autism as biomedical disorder, brain-based difference, otherworldliness, lost or stolen child and more. Our approach keeps the meaning of autism moving, always emerging, resisting, fading away and becoming again in relation to context, time, space, material oppressions, cultural scripts, intersecting differences, surprising bodies and interpretative engagement. We argue that the films we present and analyse not only significantly change and critique traditional special education approaches based on assumptions of the normative human as non-autistic, they also enact 'autism' as a becoming process and relation with implications for inclusive educators. By this we mean that the stories shift what autism might be and become, and open space for a proliferation of representations and practices of difference in and beyond educational contexts that support flourishing for all.